2016
DOI: 10.1093/aob/mcw157
|View full text |Cite
|
Sign up to set email alerts
|

Transatlantic invasion routes and adaptive potential in North American populations of the invasive glossy buckthorn,Frangula alnus

Abstract: Background and Aims Many invasive species severely threaten native biodiversity and ecosystem functioning. One of the most prominent questions in invasion genetics is how invasive populations can overcome genetic founder effects to establish stable populations after colonization of new habitats. High native genetic diversity and multiple introductions are expected to increase genetic diversity and adaptive potential in the invasive range. Our aim was to identify the European source populations of Frangula alnu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…The second study suggested that increased genetic diversity, instead of reduced genetic diversity, may have conferred greater adaptive potential in a population of glossy buckthorn introduced from a bridgehead region [29]. Due to admixture resulting from several primary introductions, the bridgehead population had high allelic richness at loci with putative ecological functions.…”
Section: Genetic Changes Taken As Evidence Of Adaptive Evolution In Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The second study suggested that increased genetic diversity, instead of reduced genetic diversity, may have conferred greater adaptive potential in a population of glossy buckthorn introduced from a bridgehead region [29]. Due to admixture resulting from several primary introductions, the bridgehead population had high allelic richness at loci with putative ecological functions.…”
Section: Genetic Changes Taken As Evidence Of Adaptive Evolution In Bmentioning
confidence: 99%
“…Two studies suggested that genetic changes could underlie greater invasiveness of bridgehead populations [13,29]. However, none of these have demonstrated a causal link between the trait change and invasion success and cannot exclude that other processes have played a role in observed trait changes.…”
Section: Genetic Changes Taken As Evidence Of Adaptive Evolution In Bmentioning
confidence: 99%
“…Biological invasions today are perceived as major components of global change, with severe negative environmental (Blackburn et al., ; Jeschke et al., ; Simberloff et al., ) and socio‐economic impacts (Vilà et al., ). To manage invasive species, it is of vital importance to identify invasion routes (De Kort, Mergeay, Jacquemyn, & Honnay, ). However, most knowledge about the transport routes of invasive species is based on historical and observational data, which are usually scarce, confusing, and sometimes inaccurate (Haydar, ; Roman, ).…”
Section: Introductionmentioning
confidence: 99%
“…One particularly damaging invasive plant is glossy buckthorn (Frangula alnus, hereafter "buckthorn"), a shrub native to Europe that has spread throughout southeastern Canada and the eastern United States (Catling andPorebski 1994, De Kort et al 2016). Similar to many invasive shrubs, buckthorn was introduced to North America in the late 18 th and early 19 th century during a period of high maritime transatlantic trade of plants from Europe to eastern North America (De Kort et al 2016). During this time, there was extensive buckthorn trade in urban ports, such as New York, which increased the genetic diversity of these populations in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…During this time, there was extensive buckthorn trade in urban ports, such as New York, which increased the genetic diversity of these populations in the United States. The high genetic diversity prevented a bottleneck effect and allowed for buckthorn to adapt quickly to rural locations and eventually spread to natural areas successfully (De Kort et al 2016). In these areas, disturbances such habitat fragmentation due to road construction and timber harvesting (Moser et al 2016) have supported the spread of invasive plants.…”
Section: Introductionmentioning
confidence: 99%